Il corpo dell’altro: Patočka e le radici dell’empatia - Terzi, Roberto (Bollettino Filosofico, 2022)
In this article, I will examine the issues of the other and empathy in Patočka’s phenomenology. I will first address the more general theme of otherness. Starting from a critique of Heidegger’s approach and an enhancement of the core of Husserlian analysis of intersubjectivity, Patočka confers a crucial role to otherness in the very constitution of the self and its relation to the world. This role is expressed in the description of the movement of sinking roots, as acceptance by the others and affective-sensible consonance with the world, which is the root of any further form of empathy. These analyses thus make it possible to delimit and redefine in an asubjective sense the relationships that the term “empathy” is intended to describe, in a phenomenological description of the structures of experience that at the same time aspires to be the basis of an existential ethics. Keywords: Empathy, Heidegger, Husserl, Otherness, Patočka